Lintasan sampah mikro plastik di kawasan konservasi perairan Nasional Laut Sawu, Nusa Tenggara Timur - Noir P Purba; Widodo S Pranowo; Sahat M. Simanjuntak; Ibnu Faizal; Haifa H. Jasmin; Dannisa I.W. Handyman; Putri G Mulyani (Depik Jurnal, 2019)
Abstract. At present, marine debris is an important issue in Indonesia. Due to the complex pattern of ocean currents, research on the distribution of marine waste in Indonesia is still very lacking. This study aims to determine the movement of microplastic particles at the Savu Sea National Marine Park. The method used was to simulate the hydrodynamic model and particle trajectory. Data used were wind, tides, bathymetry, coastline, weight of garbage, and garbage fluxes. Analysis was carried out on physical data visualization, hydrodynamic models, and particle trajectory models. The hydrodynamic model simulation shows if the average current velocity ranges from 0,0002 m/s to 0.35 m/s. The particle trajectory showed that microplastic particle movements tend to move to the south, where some of them move west and east of the Savu Sea. Besides being affected by tides, microplastic particle movements in the Savu Sea National Marine Park are also influenced by various currents that pass through the Savu Sea waters, especially by Indonesia Troughflow.